Bone-borne distractor versus tooth-borne distractor for maxillary expansion: a Systematic Review (Research, Society and Development, 2020)
The etiology of transverse maxillary deficiency is considered multifactorial, and has a deleterious effect on the bone development of the maxilla and nasal cavities, causing maxillary atresia and posterior crossbite. The objective of this systematic review was to compare in the scientific literature the effectiveness of the maxillary disjunction treated using dental distractor versus bone distractor. A systematic literature review was performed using the Science Direct, Embase, Cochrane Collaboration Library, and PubMed / MEDLINE databases. The search strategy provided a total of 119 studies. After screening by reading the titles and abstracts, seven articles met all the criteria and were included in this systematic review. Studies have shown that the choice of type of orthodontic-orthopedic appliance is directly related to the prior individualized planning of each patient. With regard to patients who are in the development phase, the recommendation is the use of dental maxillary expanders, such as the Hyrax appliance. In addition, it is not recommended to perform rapid maxillary expansion in adult patients, due to the expansion resistance that occurs in the palatine sutures. The treatment of patients with closed median palatine suture must be done by surgically assisted maxillary expansion.